Analysis of Administrative Hospital Human Resource Competence and Its Influence on Administrative Performance at Grandmed Hospital Lubuk Pakam in 2025 - Kasim, Felix; Putri Sari Maharani; Aya Sofia Diaz (JURNAL KESMAS DAN GIZI (JKG), 2025)
This study aims to analyze the competence of hospital administrative human resources (HR) and its influence on administrative performance at Grandmed Hospital Lubuk Pakam in 2025. A quantitative method with a cross-sectional design was employed. The study population consisted of all administrative staff, with 80 respondents selected using a total sampling technique. Data were collected using a structured questionnaire with a five-point Likert scale, which was tested for validity and reliability. The findings revealed that the majority of respondents had high competence (67.5%) and good administrative performance (70%). Bivariate analysis using the Chi-square test showed a significant relationship between HR competence and administrative performance (p = 0.001). Multivariate analysis with logistic regression demonstrated that HR competence had a significant effect on administrative performance, with an Odds Ratio (OR) of 6.82 (95% CI: 2.35–19.80). This indicates that staff with high competence are almost seven times more likely to demonstrate good administrative performance compared to those with moderate competence. The study highlights the importance of strengthening hospital administrative HR competence through continuous training and development to support service quality and hospital competitiveness.